Progress in the synthesis of the lituarines: stereocontrol in sequential C-C bond formation on a spirobutenolide template. - Robertson, J; Dallimore, J (2005)
[structure: see text] We describe elaboration of a tricyclic spirobutenolide corresponding to the C(7-18) tricyclic substructure common to lituarines A-C. Conjugate addition, to install the C(16) methyl, is followed by construction of the crucial C(18-19) bond by silyl enol ether addition to the derived spiroacetal C(18)-O oxonium ion. Esterification with a C(1-6) acid, and selective ozonolysis to release the C(23) carbonyl, complete the assembly of all the carbons present in the lituarine macrocyclic core.